Investigation of wear properties of elastomer modified wollastonite and hazelnut shell flour reinforced polypropylene composites - Kartal, İlyas; Mudu, Mehmet; Büyükkaya, Kenan; Demirer, Halil (İdris Karagöz, 2025)
In this study, hybrid composites were produced by using polypropylene (PP) polymer as matrix material, and hazelnut shell (HS) and wollastonite (W) as reinforcement in different ratios. Hazelnut shell flour (HSF) and wollastonite reinforced polypropylene mixtures were modified with poly(styrene-b-ethylene-co-butylene-b-styrene) (SEBS) triblock copolymer and maleic anhydride grafted SEBS (SEBS-g-MA). Wear properties of the hybrid composites were investigated as a function of elastomeric component. First, the reference hybrid composites were prepared from PP and W + HSF mixtures in the ratio of 80/10+10 by weight through extrusion method. SEBS and SEBS-g-MA modified hybrid composites (%, by weight ratios - 3, 6, 9) were then prepared by using these reference mixtures. The goal of this study is to investigate the effect of elastomeric modifications on the wear properties of the hybrid composites. Wear test samples prepared out of those mixtures by injection molding. In order to avoid any degradation due to the temperature sensitivity of the hazelnut shell, temperatures were kept close to lower limits during extrusion processing. Wear features of the samples were investigated by using an abrasion tester. Scanning electron microscopy was used for analyzing morphological features of the worn surfaces. It was found that SEBS and SEBS-g-MA modifications resulted in the reduction of the weight loss.

Bu çalışmada matris malzemesi olarak polipropilen polimer, takviye olarak ise fındık kabuğu (HS) ve volastonit (W) farklı oranlarda kullanılarak hibrit kompozitler üretilmiştir. Poli(stiren-b-etilen-ko-bütilen-b-stiren) (SEBS) triblok kopolimeri ve maleik anhidrit aşılı SEBS (SEBS-g-MA) ile modifiye edilmiş fındık kabuğu unu ve wollastonit takviyeli polipropilen karışımları. Hibrit kompozitlerin aşınma özellikleri elastomerik bileşenin bir fonksiyonu olarak araştırılmıştır. İlk olarak polipropilen (PP) ve volastonit + fındık kabuğu unu karışımlarından ağırlıkça 80/10+10 oranında ekstrüzyon yöntemiyle referans hibrit kompozitler hazırlandı. Daha sonra bu referans karışımlar kullanılarak SEBS ve SEBS-g-MA ile modifiye edilmiş hibrit kompozitler (%, ağırlık oranları - 3, 6, 9) hazırlandı. Bu çalışmanın amacı, elastomerik modifikasyonların hibrit kompozitlerin aşınma özellikleri üzerindeki etkisini araştırmaktır. Referans grubu olarak %10 W + %10 HSF dolgulu polipropilen kompozitler dikkate alındı. Bu referans grubu, hibrit kompozitin ağırlığına göre %3-6 ve %9 oranında SEBS ve SEBS-g-MA eklenerek değiştirildi. Bu karışımlardan enjeksiyonlu kalıplama yoluyla hazırlanan aşınma test numuneleri. Fındık kabuğunun sıcaklığa karşı hassasiyetinden dolayı herhangi bir bozulma yaşanmaması için ekstrüzyon işlemi sırasında sıcaklıklar alt sınırlara yakın tutuldu. Numunelerin aşınma özellikleri aşınma test cihazı kullanılarak araştırılmıştır. Aşınmış yüzeylerin morfolojik özelliklerini analiz etmek için taramalı elektron mikroskobu kullanıldı. SEBS ve SEBS-g-MA modifikasyonlarının ağırlık kaybının azalmasına neden olduğu bulunmuştur.
Elastomer modifiye wollastonit ve fındık kabuğu partikülü takviyeli polipropilen kompozitlerin aşınma özelliklerinin incelenmesi
Keywords: Composite and Hybrid Materials; Kompozit ve Hibrit Malzemeler